Cacopsylla fraudatrix sp.n. (Hemiptera: Psylloidea) recognised from testis structure and mitochondrial gene COI - Kuznetsova, Valentina G.; Labina, Eugenia S.; Shapoval, Nazar A.; Maryańska-Nadachowska, Anna; Lukhtanov, Vladimir A. (Zootaxa, 2012)
Cacopsylla fraudatrix Labina & Kuznetsova sp.n., collected from Vaccinium myrtillus in Bieszczady Mountains (S. Poland) is described and compared with the most closely related species, C. myrtilli (developing on V. myrtillus) and C. ledi (on Ledum palustre) as well as with a distantly related species C. vaccinii  (on V. bracteatum). The identity of the new species is supported by the structure of testes consisting of two follicles each, in contrast to four in C. myrtilli and C. ledi, and by a molecular phylogenetic analysis based on a 714 bp fragment of the mitochondrial COI gene. C. fraudatrix sp. n. forms a distinct clade in MP, ML and BI trees and differs from C. myrtilli by 28 fixed nucleotide substitutions (uncorrected p-distance = 3.92%) and from C. ledi by 26 fixed nucleotide substitutions (uncorrected p-distance = 3.64%).